HUBUNGAN KONSEP DIRI MATEMATIKA DENGAN PROKRASTINASI AKADEMIK PADA SISWA - Martia Ningsih; Herman Nirwana (Universitas Negeri Padang, 2019)
This study aims to look at the relationship between the mathematical self-concept and academic procrastination of students. The design of this study is a quantitative method. The population in this study were students of SMK 1 Bukittinggi. The total sample is 100 students in class X and XI for the 2017/2018 school year. Subject collection using stratified random sampling technique. Data were collected using a scale of mathematical self-concept and the scale of academic procrastination. Data analysis techniques were processed using the product moment from Karl Pearson with the help of the SPSS version 20.0 program. The correlation coefficient is obtained at r = -0, 478 with a significance value of 0.0000 (p <0.05). These results indicate that the hypothesis is accepted, which means that there is a significant negative relationship between the self-concept of mathematics and academic procrastination in students. Penelitian ini bertujuan untuk melihat hubungan konsep diri matematika dengan prokrastinasi akademik pada siswa. Desain penelitian ini adalah metode kuantitatif. Populasi dalam penelitian ini adalah siswa SMKN 1 Bukittinggi. Jumlah sampel sebanyak 100 siswa kelas X dan XI tahun ajaran 2017/2018. Pengambilan subjek menggunakan teknik stratified random sampling. Data dikumpulkan dengan menggunakan skala konsep diri matematika dan skala prokrastinasi akademik. Teknik analisis data diolah menggunakan product moment dari Karl Pearson dengan bantuan program SPSS versi 20.0. Nilai koefisien korelasi didapat sebesar r = -0, 478 dengan nilai signifikansi sebesar 0,0000 (p<0,05). Hasil tersebut menunjukkan bahwa hipotesis diterima, yang artinya terdapat hubungan negatif yang signifikan antara konsep diri matematika dengan prokrastinasi akademik pada siswa.